Epidemiology of malaria in Rohingya refugee camps in Bangladesh within 2017-2020 - Khan M.A.A. (2023)
BACKGROUND: Malaria causes significant morbidity and mortality in tropical and sub-tropical regions, particularly in humanitarian emergencies including refugee camps in malaria endemic areas. An epidemiological investigation was conducted on malaria disease distribution and risk factors in the world's largest refugee settlement, the Rohingya refugee camps on the south-eastern border area of Bangladesh, within 2017-2020. METHODS: From February 2017 to March 2020, 30,460 febrile patients were tested for malaria using light microscopy and rapid diagnostic tests. Most were self-presenting symptomatic patients and a minority were from door-to-door malaria screening. Diagnostic tests were done by trained medical technologists upon the advice of the concerned physicians in the camps. Test positivity rate (%) and annual parasite incidence were calculated and compared using chi-squared (χ 2) test or odds ratios. RESULTS: The overall average annual test positivity rate (TPR) was 0.05%. TPR was highest in people who had travelled to the forest in the previous 2 months, at 13.60%. Cases were clustered among male adults aged 15-60 years. There were no cases among children under five years or pregnant women and no deaths from malaria. CONCLUSION: This study found very few malaria cases among Rohingya refugees with the majority of cases being imported from hilly forested areas, which were thus assumed to act as the reservoir for transmission.